2005
DOI: 10.1097/01.aids.0000192088.72055.90
|View full text |Cite
|
Sign up to set email alerts
|

A framework for understanding factors that affect access and utilization of treatment for hepatitis C virus infection among HCV-mono-infected and HIV/HCV-co-infected injection drug users

Abstract: Treatment for hepatitis C virus (HCV) is rarely received by injection drug users (IDU), particularly those co-infected with HIV. We propose a framework for understanding factors that affect utilization and adherence to HCV therapy among HCV mono-infected and HIV/HCV-co-infected IDU. Provision of treatment requires calculation of risks and benefits including evaluation of a number of time-varying factors that collectively determine a gradient of treatment eligibility, advisability and acceptability, the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 81 publications
2
39
0
Order By: Relevance
“…Similarly, in a study of IDUs on methadone maintenance with expedited referrals and care, only a few participants received evaluation and treatment (Fishbein et al, 2004). The combination of current or former injection drug use, poly drug use either with or without concurrent alcohol use, psychiatric co-morbidities, low education levels, a history of incarceration, low levels of use of primary care combined with distrust of providers (or provider distrust of and reluctance to serve IDU populations), and the complexity of evaluating individuals for HCV treatment create barriers that are difficult to surmount even under optimal conditions of provider support for, and encouragement of, treatment in an IDU population (Edlin et al, 2005;Mehta et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a study of IDUs on methadone maintenance with expedited referrals and care, only a few participants received evaluation and treatment (Fishbein et al, 2004). The combination of current or former injection drug use, poly drug use either with or without concurrent alcohol use, psychiatric co-morbidities, low education levels, a history of incarceration, low levels of use of primary care combined with distrust of providers (or provider distrust of and reluctance to serve IDU populations), and the complexity of evaluating individuals for HCV treatment create barriers that are difficult to surmount even under optimal conditions of provider support for, and encouragement of, treatment in an IDU population (Edlin et al, 2005;Mehta et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…HCV is a severe illness, and once HCV is detected, follow-up care is essential. Studies have shown that the majority of IDUs are interested in receiving treatment for HCV (Stein, Maksad, & Clarke, 2001) but do not receive treatment, either because of unwillingness to follow through or because of other barriers, such as provider unwillingness to enroll this population into treatment protocols (Fishbein, Lo, Reinus, Gourevitch, & Klein, 2004;Giordano et al, 2005;Huckans, Blackwell, Harms, Indest, & Hauser, 2005;Kresina, Bruce, Cargill, & Cheever, 2005;Mehta et al, 2005;Stoove, Gifford, & Dore, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The major individual barriers to HCV treatment eligibility (low motivation, active injection drug use, alcohol use, depression) are modifiable. With appropriate treatment, coinfected persons deemed at first ineligible for HCV therapy can become eligible for therapy [30,31].…”
Section: Physician and Patient Barriers To Treatment Of Hcv In Coinfementioning
confidence: 99%
“…Longitudinal studies cite transience as a primary reason for loss-to-follow among drug using participants (Cottler, Compton, Ben Abdallah, Horne, & Claverie, 1996;Messiah, Navaline, Davis-Vogel, Tobin-Fiore, & Metzger, 2003). Social instability and uncertain living situations are frequently cited barriers to initiation and adherence to HIV and HCV therapy among injection drug users (Bouhnik et al, 2002;Mehta et al, 2005). However, this is not the case for all drug users and little is known about the differences between those who move often and those who do not.…”
Section: Introductionmentioning
confidence: 99%